Sistema de gestión de información para reportar fallos y mantenimiento de equipos biomédicos de la clínica odontológica de la Universidad Antonio Nariño, sede Popayán (2025)
The improper use of biomedical equipment has gradually become a silent enemy for healthcare service providers. The incorrect handling of these devices can lead to severe consequences that jeopardize patient safety. For this reason, the World Health Organization (WHO) has urged its member countries to prioritize patient safety as a public health issue. Currently, reports on failures and maintenance—both preventive and corrective—are recorded manually and in physical format, which significantly increases the workload. This project aims to develop an information management system through a web-based tool that stores data related to the biomedical equipment of the dental clinic at the Antonio Nariño University. The focus is on dental units and the autoclave. Additionally, it seeks to train users by employing audiovisual material that promotes the proper handling of biomedical equipment to strengthen their knowledge and reduce the frequency of failures caused by improper use. Digitizing information will reduce the use of physical paperwork, streamline processes, optimize maintenance management, and facilitate efficient access to information. Finally, the project was validated through a survey directed at direct users, obtaining a positive result in terms of acceptance and user satisfaction with its implementation.